1999
DOI: 10.1063/1.166408
|View full text |Cite
|
Sign up to set email alerts
|

Period-doubling behavior in frontal polymerization of multifunctional acrylates

Abstract: Front dynamics in the frontal polymerization of two multifunctional acrylate monomers, 1,6-hexanediol diacrylate (HDDA) and trimethylolpropane ethoxylate triacrylate (TMPTA), with Lupersol 231 [1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane] as the initiator, are studied. In most frontal polymerization systems, the dynamics are associated with a planar front propagating through the sample. However, in some cases, front behavior can be altered: the front becomes nonplanar characterized by complex patterns lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 38 publications
2
63
0
Order By: Relevance
“…Gray found that the energy of activation of HDDA increased exponentially during the reaction [100]. Applying the steady-state theory of polymerization to Gray's results, Masere et al calculated the effective energy of activation for thermally initiated polymerization (photoinitiation has no energy of activation) by including the energy of activation (E a ) of a typical peroxide [101]. They calculated that E a of HDDA polymerization increased from 80 kJ/mol at 0% conversion (which is the same as that of methacrylic acid) to 140 kJ mol −1 at 80% conversion.…”
Section: Effect Of Complex Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gray found that the energy of activation of HDDA increased exponentially during the reaction [100]. Applying the steady-state theory of polymerization to Gray's results, Masere et al calculated the effective energy of activation for thermally initiated polymerization (photoinitiation has no energy of activation) by including the energy of activation (E a ) of a typical peroxide [101]. They calculated that E a of HDDA polymerization increased from 80 kJ/mol at 0% conversion (which is the same as that of methacrylic acid) to 140 kJ mol −1 at 80% conversion.…”
Section: Effect Of Complex Kineticsmentioning
confidence: 99%
“…Masere et al studied fronts with a peroxide initiator at room temperature and used two bifurcation parameters [101]. They added an inert diluent, DMSO, to change the front temperature and observed a variety of modes.…”
Section: Effect Of Complex Kineticsmentioning
confidence: 99%
“…The studies focused on linear stability analyses, [20,21] convective instabilities, [22,23] and nonlinear dynamics of polymerization waves. [24][25][26][27] Mathematical models of frontal free-radical polymerization were proposed. Two models considered one monomer systems, or homopolymerization, and were solved numerically [28,29] and analytically.…”
Section: Introductionmentioning
confidence: 99%
“…By reducing the number of propagating radicals, the transition metal reduces the contribution of the energy of activation for the termination step, which increases the effective activation energy. 49,50 To increase the production of free radicals, two reductants were separately tested: benzoin and 6-O-palmitoyl-L-ascorbic acid. The reductant plays an important role in reestablishing the oxidation state.…”
Section: Resultsmentioning
confidence: 99%
“…Such nonplanar modes of propagation have been the subject of much investigation. 40,[45][46][47][48][49][50][51] The complexity of the front increases with the value of the effective energy of activation. By reducing the number of propagating radicals, the transition metal reduces the contribution of the energy of activation for the termination step, which increases the effective activation energy.…”
Section: Resultsmentioning
confidence: 99%